2015
DOI: 10.1128/jvi.00261-15
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Single Envelope N-Linked Glycosylation Site Enhances the Pathogenicity of Bovine Leukemia Virus

Abstract: Viruses have coevolved with their host to ensure efficient replication and transmission without inducing excessive pathogenicity that would indirectly impair their persistence. This is exemplified by the bovine leukemia virus (BLV) system in which lymphoproliferative disorders develop in ruminants after latency periods of several years. In principle, the equilibrium reached between the virus and its host could be disrupted by emergence of more pathogenic strains. Intriguingly but fortunately, such a hyperpatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
(69 reference statements)
1
23
0
3
Order By: Relevance
“…First, a mutation of the virus genome can affect the incubation period until tumor development, because in a previous study, the percentage of EBL cases associated with the L233-Tax protein was significantly higher than that associated with the P233-Tax in young cattle (26). Moreover, a mutation in an N-linked envelope glycosylation site (N230E) resulted in high provirus loads during experimental infection in sheep, which led to an accelerated pathogenesis and shortening of the incubation period (30). Second, it has been reported that certain alleles of the major histocompatibility complex class II DRB3 gene are involved in susceptibility and resistance against BLV infection (31,32).…”
Section: Discussionmentioning
confidence: 98%
“…First, a mutation of the virus genome can affect the incubation period until tumor development, because in a previous study, the percentage of EBL cases associated with the L233-Tax protein was significantly higher than that associated with the P233-Tax in young cattle (26). Moreover, a mutation in an N-linked envelope glycosylation site (N230E) resulted in high provirus loads during experimental infection in sheep, which led to an accelerated pathogenesis and shortening of the incubation period (30). Second, it has been reported that certain alleles of the major histocompatibility complex class II DRB3 gene are involved in susceptibility and resistance against BLV infection (31,32).…”
Section: Discussionmentioning
confidence: 98%
“…There is also a potential threat associated with the emergence of hyperpathogenic strains, as described in related viruses (de Brogniez et al, 2015). …”
Section: Membersmentioning
confidence: 99%
“…The replacement of asparagine with glutamic acid at codon 230 of the Env protein reportedly enhances the pathogenicity of BLV through the alteration of the N-linked glycosylation status (de Brogniez et al, 2015). However, the BLV strain in the calf in this study maintained asparagine at this site.…”
Section: Discussionmentioning
confidence: 73%